Micro learning : motivating students’ learning interests - Danilah Salleh; Norhaiza Khairudin; Marhaiza Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Psychologically, students face several problems during Online Learning which will reduce their learning interest. The students’ motivation may be dropped due to a lack of understanding of the subject since they have to face it alone or due to technical aspects like internet lagging. There are various ways done by the educator to grow the interest of students in order for them to participate in class activities. Information technology has helped educators learn various techniques in teaching and learning. The undeniable interest of students in media socials has triggered the development of enormous software to be used in teaching and learning. Micro learning is a bite-sized, small learning unit with just the necessary amount of information to help learners achieve a goal. In this study, the micro learning technique is implemented by using videos that contain simple explanations of certain topics. This study examined how the micro-learning approach can boost students learning interest by measuring their participation in class by employing qualitative action research methodology where it involved 40 accounting students. The outcome of the study showed that students’ participation is at an excellent level. Micro learning has helped boost the interest of students in their learning.